Education Policy as Public Policy - Alina Wróbel (Studia z Teorii Wychowania)
This article examines the education policy currently implemented in Poland through the lens of understanding, characteristics, and functions of public policy. The analysis is framed within a metatheoretical perspective, referencing the concept of long duration. To illustrate the practice of education policy as a form of public policy, determinations have been made regarding the nature of public policy, its theoretical foundations, aims, and practical priorities. The conclusion highlights selected examples of actions and phenomena that illustrate how education policy deviates from public policy principles, along with research examples that provide theoretical foundations for the desired changes.